Classification and properties of duricrusts for excavation purpose - Mohd. Amin, Mohd. For (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2007)
Although certain characteristics of duricrusts display a strong resemblance to clastic sedimentary rocks, in terms of lithology, they cannot be classified as rock. These ambiguities on classification may lead to several problems associated with excavation of duricrusts, particularly with regard to method used and rate of payment. In an attempt to draw some guidelines in evaluating the degree of excavatability of duricrusts, this paper highlights some of the fundamental differences and similarities between duricrusts and clastic sedimentary rocks. Laboratory and field data show that, in terms of texture and strength, duricrusts exhibit strong similarities to clastic sedimentary rocks. However, the origin of duricrusts does not fulfill the criteria for classification as rock. As such, for certain geologic materials, lithologic classification alone may not be sufficient to reflect their excavatability. Further verification on the material properties is also an essential aspect to be considered.